2007
DOI: 10.1523/jneurosci.2131-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortex Encodes Willingness to Pay in Everyday Economic Transactions

Abstract: An essential component of every economic transaction is a willingness-to-pay (WTP) computation in which buyers calculate the maximum amount of financial resources that they are willing to give up in exchange for the object being sold. Despite its pervasiveness, little is known about how the brain makes this computation. We investigated the neural basis of the WTP computation by scanning hungry subjects' brains using functional magnetic resonance imaging while they placed real bids for the right to eat differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

77
710
4
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(801 citation statements)
references
References 26 publications
77
710
4
10
Order By: Relevance
“…The thalamus serves as a critical relay structure between cortical and subcortical regions, facilitating information integration among the SN/VTA and striatum as well as prefrontal areas such as the vmPFC and dlPFC (Haber and Knutson, 2009). The vmPFC has been widely implicated in subjective value encoding Kable and Glimcher, 2007;Levy and Glimcher, 2012;Montague and Berns, 2002;Padoa-Schioppa and Assad, 2006;Plassmann et al, 2007) and has been shown to integrate value information during multi-attribute decision-making (Basten et al, 2010;Hare et al, 2011;Kahnt et al, 2011). Building on these findings, we here show that vmPFC encodes integrated cue values.…”
Section: Discussionsupporting
confidence: 65%
“…The thalamus serves as a critical relay structure between cortical and subcortical regions, facilitating information integration among the SN/VTA and striatum as well as prefrontal areas such as the vmPFC and dlPFC (Haber and Knutson, 2009). The vmPFC has been widely implicated in subjective value encoding Kable and Glimcher, 2007;Levy and Glimcher, 2012;Montague and Berns, 2002;Padoa-Schioppa and Assad, 2006;Plassmann et al, 2007) and has been shown to integrate value information during multi-attribute decision-making (Basten et al, 2010;Hare et al, 2011;Kahnt et al, 2011). Building on these findings, we here show that vmPFC encodes integrated cue values.…”
Section: Discussionsupporting
confidence: 65%
“…Again, even very young children show this pattern: a general preference for equal shares, trumped by an ingroup bias in competitive contexts [56]. Although many fMRI studies have characterized neural mechanisms for calculating value, for preferring fair outcomes and for altruistic punishment [57][58][59], none have yet looked at the effects on these neural mechanisms of active conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently consistent with Type I models, some recent work in neuroscience, especially in neuroeconomics, has been interpreted as promising a direct neural measure of value, in terms of levels of activity in key brain regions [21][22][23][24][25]. Such assumptions underpin much current economic practice, such as the use of contingent valuation methods to compare otherwise incommensurable goods (lower pollution; more car ownership) by relating them into a common ‗currency' (i.e., money).…”
mentioning
confidence: 90%